Evaluasi Beban Fisiologis Pada Aktivitas Material Handling di PT XYZ Dengan Metode Simulasi - Medi Humaedi; Habibi Husni Mubarok; Ferdian Setia Nugraha; Ridwan Adi Pamungkas; Rangga Arisandy; Fibi Eko Putra (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to evaluate the level of physiological workload that occurs during material handling activities at PT XYZ by using a simulation-based approach supported by heart rate monitoring. Due to limited access to the active production area, the researchers developed a simulation that closely represents the actual operational conditions. Five participants performed repetitive lifting of 8–10 kg loads for ten minutes as a representation of the company’s manual handling tasks. Heart rate measurements were taken in three phases: before the activity, during the task, and during the recovery period. The results show that working heart rates ranged from 105 to 122 bpm, which falls into the heavy workload category according to Tarwaka’s physiological classification (2015). These findings indicate that manual material handling places considerable physical strain on workers and requires ergonomic interventions to prevent excessive fatigue. Recommended improvements include implementing proper lifting techniques, adjusting work–rest cycles, utilizing simple assisting tools, and ensuring a more balanced distribution of workload to reduce physiological stress.